From Broadcast to Click: a Critical Review of the Media Transition in the 21st Century - Férez Vergara, José Luis; Vergara Ronquillo, Charo Jaqueline; Lázaro Crespín, Manuel Eugenio (Scripta Mundi, 2026)
The global media industry has undergone a profound transformation, shifting from a linear broadcast model to an interactive digital ecosystem, known as "click." This article presents a critical review of this transition, exploring the emerging dynamics, inherent challenges, and opportunities arising in content production and consumption. Through a qualitative methodology based on content analysis of recent academic literature (2020–2025), key concepts such as the "MediaVerse," "Craft" in content creation, "digital engagement," and "transmedia storytelling" are identified and discussed. The findings reveal a reconfiguration of professional roles, the emergence of new content strategies, and the need for constant adaptation by media organizations and academic institutions. It is concluded that this transition is a complex evolutionary process that demands a holistic understanding and an interdisciplinary approach to address its ethical, social, and technological implications.